2013
DOI: 10.1074/jbc.m113.505032
|View full text |Cite
|
Sign up to set email alerts
|

A Highly Selective Dual Insulin Receptor (IR)/Insulin-like Growth Factor 1 Receptor (IGF-1R) Inhibitor Derived from an Extracellular Signal-regulated Kinase (ERK) Inhibitor

Abstract: Background: IR/IGF-1R kinase inhibitors are promising therapeutic agents in cancer. Results: Irfin1, a compound closely related to the ERK inhibitor FR180204, inhibits IR/IGF-1R family kinases. Conclusion: Irfin1 is a remarkably selective inhibitor for the inactive states of IR/IGF-1R kinases. Significance: Broad spectrum kinase inhibitor profiling can be exploited to uncover novel targets of small-molecule compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 42 publications
0
19
0
Order By: Relevance
“…An additional limitation is that the differences in mean receptor mRNA expression across patient groups in this study are relatively small. Despite these limitations, the potential significance of our observations is highlighted by the growing interest in the role of the insulin/IGF pathway in cancer and IR/IGF1R inhibitors as potential therapies (22, 24, 26). To date, IR and IR isoforms have been understudied in the gastrointestinal tract, and our work suggests that further studies focusing on these receptors and relative IR-A and IR-B expression are needed to better understand their roles in initiation and pathophysiology of colorectal pre-cancerous lesions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An additional limitation is that the differences in mean receptor mRNA expression across patient groups in this study are relatively small. Despite these limitations, the potential significance of our observations is highlighted by the growing interest in the role of the insulin/IGF pathway in cancer and IR/IGF1R inhibitors as potential therapies (22, 24, 26). To date, IR and IR isoforms have been understudied in the gastrointestinal tract, and our work suggests that further studies focusing on these receptors and relative IR-A and IR-B expression are needed to better understand their roles in initiation and pathophysiology of colorectal pre-cancerous lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a number of studies have shown that IGF1R confers resistance to radiation therapy and chemotherapy (17, 18), and clinical evidence links IGF1R over-expression to colorectal tumor formation and progression (19, 20). Although IGF1R inhibitors showed a potential to reduce tumor growth (21, 22), recent reports suggested that IR may permit tumors to resist IGF1R inhibition, which led to the development of dual IGF1R/IR inhibitors (2326). …”
Section: Introductionmentioning
confidence: 99%
“…In addition to this set, five additional compounds were profiled: Aurora Kinase Inhibitor II (CAS no. 331770-21-9, purchased from EMD Biosciences); irfin1 (Anastassiadis et al, 2013) (CAS no. 1177970-73-8, purchased from EMD Biosciences); and afatinib (CAS no.…”
Section: Methodsmentioning
confidence: 99%
“…The specific methods outlined in this protocol for the dot blot kinase assay were used to examine small-molecule inhibition of the insulin receptor kinase domain (11) but these methods can be generalized for examining inhibition of other kinase targets. Reaction conditions such as buffer components, concentration and type of substrates, as well as temperature and time may need to be optimized for kinases other than the insulin receptor kinase.…”
Section: Introductionmentioning
confidence: 99%
“…We perform anion exchange chromatography followed by gel filtration chromatography in order to obtain kinase that is >90% pure by SDS-PAGE. Details of the expression and purification of the insulin receptor kinase can be found in Duong-Ly et al (11) and Wei et al (13). After purification, we store the kinase in small one-time use aliquots at −80°C to preserve catalytic activity.…”
mentioning
confidence: 99%